2016
DOI: 10.15171/joddd.2016.025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ameloblastoma and keratocystic odontogenic tumor on the displacement pattern of inferior alveolar canal in CBCT examinations

Abstract: Background. The inferior alveolar canal should be examined as a significant anatomical landmark, particularly in the posterior body and ramus of the mandible, for dental and surgical procedures. In the present study, the effects of two pathological lesions, ameloblastoma and keratocystic odontogenic tumor, on canal displacement were investigated.Methods. This study had a single-blinded design. Twenty-six patients with lesions in the mandible referred to Imam Reza Hospital, Tabriz, Iran, were studied in two equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…1012 Odontogenic keratocysts grow in the anterior-posterior direction in the jawbone and do not cause considerable expansion 10. According to Abdi et al,4 53.8% of odontogenic keratocysts caused buccal displacement, while 46.2% caused lingual displacement of the IANC. Moreover, Farman et al9 found that odontogenic keratocysts may cause slight downward displacement of the IANC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1012 Odontogenic keratocysts grow in the anterior-posterior direction in the jawbone and do not cause considerable expansion 10. According to Abdi et al,4 53.8% of odontogenic keratocysts caused buccal displacement, while 46.2% caused lingual displacement of the IANC. Moreover, Farman et al9 found that odontogenic keratocysts may cause slight downward displacement of the IANC.…”
Section: Resultsmentioning
confidence: 99%
“…Ameloblastoma can cause displacement of the adjacent teeth, root resorption, and/or extensive bone expansion 19. According to Abdi, 84.6% of ameloblastomas cause buccal displacement of the IANC, and 15.4% cause lingual displacement 4. According to Kolokythas et al,17 buccal displacement of the IANC caused by odontogenic tumors may be explained based on the relationship of the developing tooth bud with the IANC and its contents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ameloblastomas cause buccal displacement of the inferior alveolar nerve (IAN) in 84.6% of cases and lingual displacement in 15.4%. 5 When treating patients with ameloblastoma, it is essential to know the pathway of the mandibular canal when determining the direction of biopsy access and the safety limits of surgical excision in order to prevent neurovascular injuries. 5 6 Precise localization of the IAN may be particularly crucial for posterior mandibular lesions, especially if preservation of the neurovascular bundle is included in the surgical planning.…”
Section: Introductionmentioning
confidence: 99%
“…At this location, the inferior alveolar nerve branches into the incisive and mental nerves. The distance between the mandibular canal and the buccal cortical plate in the molar region is greater than that in the ramus region, and may vary from 0.57 mm to 5.8 mm in the ramus region and from 0.40 mm to 70 mm in the molar region 12. The mandibular canal has several normal anatomical variations, such as a bifid canal, a trifid canal, or an enlarged canal 13.…”
Section: Introductionmentioning
confidence: 99%